Enterprise Resource Planning, Accounting Information System Quality, Competence, and Internal Control on Company Performance - Adelia Aura Az Zahra; I Nyoman Wijana Asmara Putra (E-Jurnal Akuntansi, 2024)
The study's objective is to learn how PT Perusahaan Listrik Negara Indonesia Power Bali Power Generation Unit's enterprise resource planning deployment, accounting information system quality, human resource proficiency, and internal control systems have influenced the firm's performence. There were 175 workers included in the sample. Purposive sampling was used to choose the sample size of 48 respondents. Multiple liner regression analysis was used to examine the data. A favorable and statistically significant correlation was established between enterprise resource planning installation, accounting information system quality, human resource competency, and internal control system maturity and financial performance. The quality of accounting information systems, qualified competences, and an efficient internal control system will all contribute to optimizing and improving the company's performance when enterprise resource planning with a good performance is implemented.